Effect of Intelligent Reflecting Surface on WSN Communication With Access Points Configuration - Mahmoud Z. Iskandarani (IEEE Access)
As signal quality and communication channel reliability is critical for wireless communication, and to overcome some of the negative effects affecting the transmitted signals and data, due to environment and line-of-sight problems, and to enable internet based, on-line, and IoT applications, the use of Intelligent Reflecting Surface devices (IRS) become critical. Thus, this work objective is to simulate, model, and analyze parameters that are critical to the quality of transmitted signal over a wireless network and a WSN sensor nodes arrangement. The successful simulation, mathematical modeling, and analysis used Signal-to-Noise Ratio (SNR) as a calibrating parameter to enable design and optimization of a network consisting of WSN sensor nodes, access points (APs), and IRS using two arrangements for the purpose of comparison between direct communication (Nodes-APs), and indirect communication (Nodes-IRS-APs). This enabled direct and indirect WSN sensor node communication and provided a comparison of how effective an IRS can be on improving the Quality of links and communication channel in a wireless network. The work looked at three distinct, but related cases of SNR covering IRS elements, access point numbers, and IRS location. Several simulation runs are carried out, in order to show effect of geometrical distribution of WSN sensor nodes, access points, and IRS, with averaging at the end to obtain an overall comparison between direct and indirect communication paths, and to enable mathematical modeling, as random distribution is introduced in the simulation. The simulation and subsequent analysis showed effectiveness of increasing IRS elements, and access points on improving SNR, and proved that better SNR or optimum SNR can be obtained when the IRS is at the center point within the application area. Exponential and incrementing function is found describing both effect of IRS elements and access point numbers in relation to SNR. Also, higher SNR is found when the IRS is at the center or middle lines compared to the corners. Mathematical expressions are developed, and relation between access point number and number of IRS elements is established. This simulation is critical in terms of design, as it shows the spread of the SNR values in relation to both WSN sensor nodes and access points graphically and analytically.